Roadian-Wordian (Guadalupian, Middle Permian) global palaeobiogeography of brachiopods - Shen, Shu-zhong (沈树忠); Xie, Jun-fang (谢俊芳）; Zhang, Hua (张华）; Shi, G. R. (Global and Planetary Change, 2009)
A database of 4471 Roadian-Wordian (Guadalupian, Middle Permian) occurrences of 381 brachiopod genera in 44 different operational geographical units (stations) was analyzed by both Q-mode and R-mode quantitative methods. Four distinct brachiopod biogeographical realms and nine provinces, and 11 brachiopod associations are recognized. The Boreal Realm in the Northern Hemisphere includes the Verkolyman Province in the northern and northeastern Siberian Platform and the eastern European Province in the Ural seaway between the European and Siberian platforms. Both provinces are characterized by containing typical Boreal cold-water brachiopod associations. The Gondwanan Realm in the south also includes two provinces. The Austrazean Province in eastern Australia and New Zealand is probably the most stable province throughout the Permian and characterized by typical Gondwanan brachiopod associations. The Westralian Province centered in Western Australia is also characterized by typical Gondwanan brachiopods, but also demonstrates biogeographical links with the Tethyan stations. The Palaeoequatorial Realm located mainly in the palaeotropical zone contains highly diverse and abundant brachiopod faunas. Two regions/subrealms and four provinces are recognized within this realm. The North America Subrealm contains a distinct Grandian Province characterized by many endemic brachiopod genera and a few cold-water genera. East-central Alaska and Yukon Territory may constitute another brachiopod province. All the stations in the Tethyan Ocean (both Palaeotethys and Neotethys) constitute a distinct Asian-Tethyan Region/Subrealm and incorporate three different provinces. The Cathaysian Province is comprised of the stations in South China and its surrounding terranes/blocks and a few stations in the northern and western margin of the Palaeotethys. Two transitional provinces (Sino-Mongolian-Japanese Province and Cimmerian Province) in the northern and southern temperate zones are also recognizable. The brachiopod fauna from the Mino ...